Bioactive Steroids with Structural Diversity from the South China Sea Soft Coral Lobophytum sp. and Sponge Xestospongia sp. - Lin-Mao Ke; Zi-Ru Zhang; Song-Wei Li; Yan-Bo Zeng; Ming-Zhi Su; Yue-Wei Guo (Marine Drugs)
A chemical investigation of the soft coral Lobophytum sp. and the sponge Xestospongia sp. from the South China Sea led to the isolation of five steroids, including two new compounds (1 and 4) and one known natural product (3). Compounds 1–3 were derived from the soft coral Lobophytum sp., while 4 and 5 were obtained from the sponge Xestospongia sp. The structures of these compounds were determined by extensive spectroscopic analysis, the time-dependent density functional theory–electronic circular dichroism (TDDFT-ECD) calculation method, and comparison with the spectral data previously reported in the literature. The antibacterial and anti-inflammatory activities of isolated compounds were evaluated in vitro. Compounds 1–3, 4, and 5 exhibited weak antibacterial activity against vancomycin-resistant Enterococcus faecium G1, Streptococcus parauberis KSP28, Photobacterium damselae FP2244, Lactococcus garvieae FP5245, and Pseudomonas aeruginosa ZJ028. Moreover, compound 3 showed significant anti-inflammatory activity by inhibiting lipopolysaccharide (LPS)-induced NO production in RAW 264.7 cells, with an IC50 value of 13.48 μM.